Independent Evaluation Office Annual Report 2017. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2017)
This paper discusses that the Independent Evaluation Office (IEO) has also launched three new evaluations-which will analyze the IMF's role on fragile states, its financial surveillance activities, and its advice on unconventional monetary policies-and two evaluation updates-which will look into the IMF's exchange rate policy advice and structural conditionality. The evaluation found that, for the most part, the IMF's euro area surveillance identified the right issues during the pre-crisis period but did not foresee the magnitude of the risks that would later become paramount. The IMF's surveillance of the financial regulatory architecture was generally of high quality, but staff, along with most other experts, missed the buildup of banking system risks in some countries. The report found several issues with the way decision making was managed by the IMF. In May 2010, the IMF Executive Board approved a decision to provide exceptional access financing to Greece without seeking preemptive debt restructuring, even though its sovereign debt was not deemed sustainable with a high probability.